Protective Effects of the mTOR Inhibitor Everolimus on Cytoskeletal Injury in Human Podocytes Are Mediated by RhoA Signaling - Jeruschke, Stefanie (Public Library of Science, 2013)
Podocytes are highly differentiated kidney cells playing an important role in maintaining the glomerular filtration barrier. Particularly, the integrity of the actin cytoskeleton is crucial as cytoskeletal damage associated with foot process effacement and loss of slit diaphragms constitutes a major aspect of proteinuria. Previously, the mammalian target of rapamycin (mTOR) was linked to actin regulation and aberrant activity of the kinase was associated with renal disease. In this study, actin-related effects of mTOR inhibition by the immunosuppressant everolimus (EV) were investigated in human podocytes using an in vitro model of puromycin aminonucleoside (PAN) induced proteinuria. EV substantially recovered aberrant podocyte behavior by re-establishing a stationary phenotype with decreased migration efficiency, enhanced cell adhesion and recovery of actin stress fibers. Biochemical studies revealed substantial increase in the activity of RhoA and the effector pathway Rho-associated protein kinase (ROCK) and myosin light chain (MLC) by EV, all known regulators of stress fiber generation. Taken together, we show for the first time cytoskeleton stabilizing effects of the mTOR inhibitor EV and establish RhoA signaling as a key mediator in this process.